In vivo free‐breathing DTI and IVIM of the whole human heart using a real‐time slice‐followed SE‐EPI navigator‐based sequence: A reproducibility study in healthy volunteers. Issue 1 (24th August 2015) - Moulin, Kevin; Croisille, Pierre; Feiweier, Thorsten; Delattre, Benedicte M.A.; Wei, Hongjiang; Robert, Benjamin; Beuf, Olivier; Viallon, Magalie
Abstract : Purpose: In this study, we proposed an efficient free‐breathing strategy for rapid and improved cardiac diffusion‐weighted imaging (DWI) acquisition using a single‐shot spin‐echo echo planar imaging (SE‐EPI) sequence.Methods : A real‐time slice‐following technique during free‐breathing was combined with a sliding acquisition‐window strategy prior Principal Component Analysis temporal Maximum Intensity Projection (PCAtMIP) postprocessing of in‐plane co‐registered diffusion‐weighted images. This methodology was applied to 10 volunteers to quantify the performance of the motion correction technique and the reproducibility of diffusion parameters.Results : The slice‐following technique offers a powerful head–foot respiratory motion management solution for SE‐EPI cDWI with the advantage of a 100% duty cycle scanning efficiency. The level of co‐registration was further improved using nonrigid motion corrections and was evaluated with a co‐registration index. Vascular fraction f and the diffusion coefficients D and D* were determined to be 0.122 ± 0.013, 1.41 ± 0.09 × 10 −3 mm 2 /s and 43.6 ± 9.2 × 10 −3 mm 2 /s, respectively. From the multidirectional dataset, the measured mean diffusivity was 1.72 ± 0.09 × 10 −3 mm 2 /s and the fractional anisotropy was 0.36 ± 0.02.Conclusion : The slice‐following DWI SE‐EPI sequence is a promising solution for clinical implementation, offering a robust improved workflow for further evaluation of DWI in cardiology. Magn Reson Med 76:70–82, 2016. © 2015 Wiley Periodicals, Inc.